Welch-Powell Algorithm Implementation In Compiling Lecture Schedules In The Mathematics Education Study Program, Manado State University - Fernando Febrianto Kawatu; James U. L. Mangobi; Vivian E. Regar (International Forum of Researchers and Lecturers, 2023)
This study aims to compile a Lecture Schedule at the Mathematics Education Study Program, Faculty of Mathematics Natural and Earth Sciences Manado State University using the Welch-Powell Algorithm. The scheduling of lectures at the Mathematics Education Study Program, Faculty of Mathematics and Natural Sciences, Manado State University often collides because several lecturers have different numbers of courses and credit rights. This it can be seen that the method of preparing lectures used is still not effective and efficient. Preparation of a course schedule is an action taken so that time can be managed as effectively and efficiently as possible. The preparation of this lecture schedule will use a simple graph with input data, namely the number of lecturers, number of courses, credits for each course, days used in the week, time slots and number of classes used. After getting the input data, point coloring is carried out in coloring on the graph using the Welch-Powell Algorithm assisted by MATLAB software to get an effective and efficient class schedule. Lecture Schedule Arrangement in the Mathematics Education Study Program, Department of Mathematics, Faculty of Mathematics, Natural and Earth Sciences, Manado State University using the Welch-Powell Algorithm produces a schedule that does not collide, so that the Welch-Powell Algorithm can help prepare an effective and efficient class schedule .